An asymmetrically derivatized 1,2,3-triphospholide: synthesis and reactivity of the 4-(2'-pyridyl)-1,2,3-triphospholide anion. - Turbervill, R; Goicoechea, J (2013)
Reactions between anionic heptaphosphide clusters ([P7](3-)/[HP7](2-)) and 2-ethynylpyridine yielded the 4-(2'-pyridyl)-1,2,3-triphospholide anion ([P3C2H(2-C5H4N)](-); 1). This species was isolated as a compositionally pure [K(2,2,2-crypt)](+) salt in moderate yields. Preliminary coordination studies of 1 toward Mo(CO)6 or Mo(py)3(CO)3 (py = pyridine) afforded the diamagnetic piano-stool complex [{η(5)-P3C2H(2-C5H4N)}Mo(CO)3](-) (2). By contrast, reaction of 1 with Mo(COD)(CO)4 (COD = 1,5-cyclooctadiene) yielded [{κ(2)P,N-P3C2H(2-C5H4N)}Mo(CO)4](-) (3) which readily loses a carbonyl on heating to give 2. Reaction of 2 with Mo(COD)(CO)4 afforded the bimetallic system [{μ:η(5),κ(2)P,N-P3C2H(2-C5H4N)}{Mo(CO)3}{Mo(CO)4}](-) (4).